AN ANALYSIS OF HOTEL GRIYA SINTESA MUARA ENIM EMPLOYEES’ ABILITY TO COMPREHEND ENGLISH-BASED HOTEL INFORMATION SYSTEMS - Indah Wati; Muhammad Taslim; Destra Amni; Luthfia Renalda Tania; Muhammad Luthifar Syach Anwar (English Language Education Program, Faculty of Education and Teacher Training, Sulthan Thaha Saifuddin State Islamic University of Jambi, 2025)
In the hospitality industry, hotel information systems are predominantly operated in English, presenting linguistic challenges for staff with limited proficiency in English. This study aims to analyze the English comprehension ability of employees at Hotel Griya Sintesa Muara Enim, with a particular focus on their understanding of English-based hotel information systems. Using a quantitative descriptive approach, data were collected through a written vocabulary test (comprising 20 multiple-choice and matching items), semi-structured interviews, and documentation from 30 front-office and operational staff members. Descriptive statistical analysis revealed an average correct-response rate of 69.2% (mean score = 70.5), placing overall comprehension in the “Paham” (Understand) category. While most employees could operate the system functionally, difficulties persisted with technical terms such as PMS, interface, database error, and backup file. Key contributing factors include limited prior English training, infrequent exposure to technical vocabulary, and reliance on peer assistance. The findings suggest that staff's functional English proficiency is sufficient for daily operations but requires targeted support to enhance accuracy and confidence. Recommendations include implementing English for Hospitality Systems training, developing an in-house English terminology glossary, and establishing an internal mentoring program. This study underscores the importance of integrating language support into hospitality technology adoption to ensure operational efficiency and service quality.